ANALISIS PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMAN 11 MUARO JAMBI - ⁠Anggi Karunia Wijayanti; Muhammad Arif Liputo; Sahara (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the implementation, challenges, and solutions in applying the Merdeka Curriculum in Economics subjects for Grade XI Social Science students at SMAN 11 Muaro Jambi. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving the principal, curriculum vice principal, teachers, and students. The results show that the Merdeka Curriculum has been implemented through project-based learning, various assessment types, and the use of ATP and teaching modules. However, teachers face obstacles in planning, implementing, and evaluating learning, including limited media, time constraints, and insufficient technological skills. To overcome these issues, teachers collaborate through teacher working groups, develop independent teaching materials, and participate in training. These findings highlight the importance of continuous support for teachers in effectively implementing the Merdeka Curriculum.